2020
DOI: 10.1002/ange.202007895
|View full text |Cite
|
Sign up to set email alerts
|

Regenerable Covalent Organic Frameworks for Photo‐enhanced Uranium Adsorption from Seawater

Abstract: Uranium is a key resource for the development of the nuclear industry, and extracting uranium from the natural seawater is one of the most promising ways to address the shortage of uranium resources. Herein, a semiconducting covalent organic framework (named NDA‐TN‐AO) with excellent photocatalytic and photoelectric activities was synthesized. The excellent photocatalytic effect endowed NDA‐TN‐AO with a high anti‐biofouling activity by generating biotoxic reactive oxygen species and promoting photoelectrons to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…25,26 However, most reported amidoxime-based COFs, such as COF-TpDb-AO 11 and o-TDCOF, 9 are linked by dynamically reversible imine bonds and may undergo hydrolysis under extreme conditions, which greatly impedes the real utilization of COFs. 25 To overcome this challenge, a new class of carbon-carbon double-bond linkage sp 2 carbonconjugated COFs, including sp 2 c-COF, 27 TP-COF, 25 g-C 34 N 6 -COF, 28 NDA-TN, 29 and TFPT-BTAN COF, 26 was reported and synthesized by the Knoevenagel condensation reaction. Compared with other imine-linked COFs, sp 2 carbon-conjugated COFs, benefiting from the C=C linkages, have an excellent chemical stability even exposed to strong acidic, alkaline, and radiation conditions, 25,26 which is a prerequisite for the extraction of uranium from seawater.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 However, most reported amidoxime-based COFs, such as COF-TpDb-AO 11 and o-TDCOF, 9 are linked by dynamically reversible imine bonds and may undergo hydrolysis under extreme conditions, which greatly impedes the real utilization of COFs. 25 To overcome this challenge, a new class of carbon-carbon double-bond linkage sp 2 carbonconjugated COFs, including sp 2 c-COF, 27 TP-COF, 25 g-C 34 N 6 -COF, 28 NDA-TN, 29 and TFPT-BTAN COF, 26 was reported and synthesized by the Knoevenagel condensation reaction. Compared with other imine-linked COFs, sp 2 carbon-conjugated COFs, benefiting from the C=C linkages, have an excellent chemical stability even exposed to strong acidic, alkaline, and radiation conditions, 25,26 which is a prerequisite for the extraction of uranium from seawater.…”
Section: Introductionmentioning
confidence: 99%
“…3F & Table S4 †). 4,16,17,20,[50][51][52][53][54][55][56][57][58] When incubating in simulated seawater containing U(VI) (0.33 mg L À1 ) together with many competing metal ions (e.g., V(V) (0.183 mg L À1 ), Cu 2+ (0.1 mg L À1 ), Fe 3+ (0.34 mg L À1 ), Ni 2+ (0.66 mg L À1 ), Zn 2+ (0.5 mg L À1 ), Na + (1.08 Â 10 4 mg L À1 ), Ca 2+ (413 mg L À1 ), Mg 2+ (1.29 Â 10 3 mg L À1 ) and K + (400 mg L À1 )), the nanobrils also gave a higher equilibrium uptake for U(VI) of 27 mg g À1 than other competing metal ions (Fig. S14 †).…”
Section: Resultsmentioning
confidence: 99%
“…Cui et al. 232 synthesized the highly planar conjugated naphthalene-based sp 2 -carbon COF NDA-TN-AO and interrupted π-conjugated COF NDA-TN-AO ( Figures 5 A and 5B). The ESI and photocurrent response measurements have demonstrated that COF NDA-TN-AO outperforms COF BDA-TN-AO , indicating a much more efficient separation of charge carriers and interfacial charge transfer in the highly planar π-conjugated COF NDA-TN-AO skeleton.…”
Section: Removal Of Radionuclides By Cof-based Materialsmentioning
confidence: 99%